Sosialisasi Strategi Pencegahan Kekerasan Seksual Terhadap Anak melalui Sosialisasi UU No. 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual bagi Remaja Negeri Lumoli, Kabupaten Seram Bagian Barat - Yondri Siletty; Deassy J. A. Hehanussa (Jurnal Nusantara Berbakti, 2024)
The current rise in cases of sexual violence against children is certainly a condition of great concern in law enforcement in Indonesia. Sexual violence as a crime of morality not only has a very serious and traumatic impact on the victim but also on the family, community and country. Looking at the reality of society, cases of sexual violence often occur repeatedly and continuously, but not many people understand and are sensitive to this issue. Therefore, this service is carried out with the aim of increasing public understanding of Law No. 12/2022 concerning the Crime of Sexual Violence as a Legal Instrument in preventing and recognizing sexual violence. This service method uses a PAR (Participatory, Action, Research) approach which is implemented through outreach activities. The results obtained are increasing community understanding and participation in preventing sexual violence, especially against children.